Tracking the signature of low symmetry environments in the XAS K pre-edge - Hunault, Myrtille; Haverkort, Maurits W. (Journal of physics. Conference Series, 2016)
For Co-containing crystalline compounds measured by XAS, the influence of the local symmetry on the K pre-edge features is studied using advanced Ligand Field Multiplet (LFM) calculations, which accurately take into account the p-d hybridization. The LFM theory is used to calculate the K pre-edge spectra of Co 2+ in various environments and the absolute intensities of electric-quadrupole and -dipole transitions involved in the pre-edge. This enables to reproduce the spectra for cubic (O h , T d ) and lower symmetries (C 4v , D 3h ), and allows quantitative derivation of the local p-d mixing.